A mentor assisted program of study (MAPS) for spreadsheet applications in first year accounting: a descriptive study - Gregory Kenneth Laing,; Ronald William Perrin, (Penerbit Universiti Kebangsaan Malaysia, 2013)
The purpose of this paper is to examine the perceptions of students involved in a mentoring program. The approach involved the provision of supplemental instruction conducted in the form of a mentoring program designed to address spreadsheet applications for first year accounting tasks. Surveys were conducted over the semester and at the conclusion of the semester to obtain the mentees and mentors satisfaction with the mentoring program. Responses to surveys conducted during semester showed a high level of satisfaction with the progress from the MAPS intervention. Overall the mentees rated the MAPS intervention as being slightly beneficial to their learning and knowledge regarding the use of spreadsheet applications for accounting tasks. The practical implications from this study are that the supplemental instruction conducted in the form of a student mentoring program has the potential to influence student satisfaction with the learning process.